1998
DOI: 10.1021/jp970466c
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Model Study of the Mechanism of Chlorine Nitrate Hydrolysis on Ice

Abstract: The hydrolysis of chlorine nitrate ClONO 2 + H 2 O f HOCl + HNO 3 on a type-II polar stratospheric cloud ice aerosol is modeled via the ClONO 2 ‚(H 2 O) 3 reaction system at the HF/6-31+G** level of theory with microsolvation by three additional STO-3G waters, and with electron correlation accounted for at the MP2 level. The calculations suggest a fast reaction, consistent with experimental observations, and portray a transition state that involves a nucleophilic attack of a water molecule on chlorine concerte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
156
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(181 citation statements)
references
References 39 publications
24
156
1
Order By: Relevance
“…Vincent et al 64 elucidated the mechanism of oxidation of SO 2 by H 2 O 2 in water droplets, whereas Smith et al 65 examined the process of acid dissociation in water clusters. Our recent calculations concerning the hydrolysis of ClONO 2 , 52,53 in addition to the work of Bianco and Hynes, 49 have shown these prototypical clusters to suitably reproduce the observed reactivity of the PSC surface and small water droplets. Models that represent the local adsorption site by fragments excised from an ideal ice lattice 58,60 may not account for the solvating effect of the ice surface beyond the adsorption site.…”
Section: Modeling Small Water Droplets and The Ice Surfacementioning
confidence: 69%
“…Vincent et al 64 elucidated the mechanism of oxidation of SO 2 by H 2 O 2 in water droplets, whereas Smith et al 65 examined the process of acid dissociation in water clusters. Our recent calculations concerning the hydrolysis of ClONO 2 , 52,53 in addition to the work of Bianco and Hynes, 49 have shown these prototypical clusters to suitably reproduce the observed reactivity of the PSC surface and small water droplets. Models that represent the local adsorption site by fragments excised from an ideal ice lattice 58,60 may not account for the solvating effect of the ice surface beyond the adsorption site.…”
Section: Modeling Small Water Droplets and The Ice Surfacementioning
confidence: 69%
“…The fact that the yield decreases as increasing methane concentration may exclude the possibility of a methane cluster ion. In addition, the close resemblance between the contour pattern of 31 amu species and that of 3 CH + suggests the same mother cluster for both species, namely (CH 4 ) 1-2 (H 2 O) [1][2] . From these observation, this species likely to be CH 3 O + , which is synthesized in the water-methane heterocluster.…”
Section: Water and Methane Coadsorbed On Solid Nementioning
confidence: 86%
“…The role of the ice surface as a stage of chemical reaction has been studied in the wide variety of fields such as interstellar astrophysics [1], atomospheric science [2,3], and biological science. Specifically in the interstellar astrophysics [4], it is considered that the ice surface of the interstellar dust provides the stage where a complex organic molecule is synthesized from simple molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As for the net Cl 2 -producing reaction itself, one suggestion was that it occurred in two steps, the first being the hydrolysis of chlorine nitrate, ClONO 2 + H 2 O → HOCl + HNO 3 , followed by HCl+ HOCl → H 2 O + Cl 2 . Postdoc Roberto Bianco and I found the hydrolysis on a model of ice to be quite facile, courtesy of a proton relay chain (PRC) that assisted both water's nucleophilic attack on ClONO 2 's (electropositive) Cl atom and the stabilization of the NO − 3 leaving group (139). But later evidence suggested that the single-step mechanism cited above was in fact more likely, and indeed, our examination of the HCl + ClONO 2 reaction on modeled ice showed this reaction to also be facile, with once again crucial PRC assistance (140).…”
Section: Atmospheric Interstellar Biological and Renewable Energy mentioning
confidence: 99%